Cellulomonas fulva sp. nov., isolated from oil-contaminated soil. Issue 1 (31st January 2022) - Dahal, Ram Hari; Kim, Jungmin; Kim, Dong-Uk; Dong, Ke; Hong, Yongseok; Chaudhary, Dhiraj Kumar
Abstract : A yellow-coloured, Gram-stain-positive, motile, aerobic and rod-shaped bacteria, designated DKR-3 T, was isolated from oil-contaminated experimental soil. Strain DKR-3 T could grow at pH 5.0–10.5 (optimum, pH 7.0–8.5), at 10–40 °C (optimum, 25–32 °C) and tolerated 3.5 % of NaCl. Phylogenetic analyses based on its 16S rRNA gene sequence indicated that strain DKR-3 T formed a lineage within the family Cellulomonadaceae and was clustered with members of the genus Cellulomonas . Strain DKR-3 T had highest 16S rRNA gene sequence similarities to Cellulomonas gelida DSM 20111 T (98.3 %), Cellulomonas persica JCM 18111 T (98.2 %) and Cellulomonas uda DSM 20107 T (97.8 %). The predominant respiratory quinone was tetrahydrogenated menaquinone with nine isoprene units [MK-9(H4 )]. The principal cellular fatty acids were anteiso-C15 : 0, C16 : 0 and anteiso-C17 : 0 . The major polar lipids were diphosphatidylglycerol and phosphatidylglycerol. The cell-wall diamino acid was l -ornithine whereas rhamnose and glucose were the cell-wall sugars. The DNA G+C content was 74.2mol %. The genome of strain DKR-3 T was 3.74 Mb and contained three putative biosynthetic gene clusters. The average nucleotide identity and digital DNA–DNA hybridization relatedness values between strain DKR-3 T and its phylogenetically related members were below the species threshold values. Based on a polyphasic study, strain DKR-3 T represents a novel species belonging to the genus Cellulomonas, for which the name Cellulomonas fulva sp. nov. is proposed. The type strain is DKR-3 T (=KACC 22071 T =NBRC 114730 T ).